Analisis Kinerja Keuangan Pemerintah Daerah Berdasarkan Perspektif Kinerja Keuangan ( Studi Kasus Kabupaten Keerom Tahun Anggaran 2020) - Simanjuntak, Renova; Sitohang Andi Lolo, Tantry (Ridwan Institute, 2025)
The purpose of this study is to determine the financial performance of the Regional Government based on the perspective of the financial performance of Keerom Regency in 2020 by using the financial ratio to the Budget and Balance Sheet Realization Report of Keerom Regency for the 2019-2020 fiscal year. The research method used is quantitative descriptive using secondary data, namely the Regional Government Financial Statements for 2019 – 2020. The data analysis technique used is qualitative descriptive by calculating financial ratios, namely; 1) Regional Independence Ratio, 2) Effectiveness Ratio, 3) Efficiency Ratio, 4) Growth Ratio, 5) Operating Expenditure Ratio, 6) Capital Expenditure Ratio and 7) Current Ratio. The results of the calculations obtained show that Keerom Regency in 2020 has a low independence predicate, is less effective in realizing PAD, is inefficient in realizing PAD, experiences negative PAD growth, experiences an increase in operating expenses, experiences a decrease in capital expenditure and has a debt that is larger than the lancer asset so that the lancer asset cannot cover the lancer debt in a year.